Siklus Hidup Organisasi dan Strategi Peningkatan Tata Kelola SMA Santa Maria di Pekanbaru - Anna Maria (Gapenas Publisher, 2022)
SMA Santa Maria is a private educational institution in Pekanbaru under supervision of Yayasan Prayoga Riau. Organizational life cycle of SMA Santa Maria commenced when it was founded in 1975. Having achieved many accomplishments since the establishment had brought notable progress. External development and presence of competitors over time became challenges which need immediate response from school management team to improve those accomplishments, thus it was positioned at growth stage. The school management team had discussed it and decided to initiate a seminar and interactive dialogue “Organizational Life Cycle and Strategies for improving Governance at SMA Santa Maria” held on May 14 2022. It began with opening ceremony, presentation, discussion and interactive dialogue. The discussion formulated some strategies: a) reviewing vision and mission, b) collecting feedback on school performance quality and student satisfaction index on school performance analyzed with Important-Performance Analysis (IPA) method, c) setting priority on investment based on results of IPA method. Finally, school management team needs to conduct implementation control so that SMA Santa Maria is able to maintain organizational cycle at growth stage and avoid the decline stage